Listening as a Teacher: Educative Listening, Interruptions and Reflective Practice - English, Andrea (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2009)
In this inquiry, I ask what is distinctive about listening as a teacher. I develop the meaning of educative listening as a mode of listening to interruptions in a way that promotes students’ thinking and learning. Interruptions in a teacher’s listening are defined as any unexpected response from a student to the material presented — for example, a challenging viewpoint, a difficult question, or a confusing reply — that opens up possibilities for cultivating learning. To begin, I draw upon Dewey to examine the connections between listening and learning in teacher-student interaction. In the second section, I explicate the implications of Dewey’s theory of learning for a theory of listening in reflective teaching. Here, I contend that reflective teaching entails educative listening. In the final section, I inquire into how teacher education can productively address the connections between learning to listen and learning to teach reflectively.